FACTORS THAT INCREASE PURCHASE INTENTION OF ELECTRIC CARS IN JAKARTA - Ruslim, Tommy Setiawan; Setiawan, Kevin; Hapsari, Claudia Gita; Herwindiati, Dyah Erny (International Journal of Application on Economics and Business, 2023)
Global warming has become an issue for the whole world until now. The cause of global warming is air pollution produced by engine fuels from various automotives that can produce carbon dioxide. This encourages people to be more concerned about the environment, including the automotive industry. The rise of the movement to care for the environment encourages automotive companies to make electric car products which can be a solution to reduce pollution. In recent years, electric cars have started to enter the market in Indonesia. However, this is not well received by the Indonesian people. This is related to the low purchase intention of the electric car itself. The purpose of this study was to determine empirically the effect of attitude, subjective norm, perceived behavioral control, and price sensitivity on consumer purchased intention of electric cars in Jakarta. This study uses data collected from 153 respondents who are people who at least are undergoing undergraduate studies and have knowledge of electric cars in Jakarta. The data was obtained by distributing an online questionnaire in the form of a google form through social media. The data is then processed using SmartPLS 3.2.9 software. The results of this study are attitude, subjective norm, and price sensitivity have a positive and significant influence on the purchase intention of electric cars in Jakarta. Meanwhile, perceived behavioral control has no effect on the purchase intention of electric cars in Jakarta.